Environmental impacts of commuting modes in Lisbon: A life-cycle assessment addressing particulate matter impacts on health. Issue 9 (21st October 2019) - Bastos, Joana; Marques, Pedro; Batterman, Stuart A.; Freire, Fausto
Abstract: A life-cycle assessment of commuting alternatives is conducted that compares six transportation modes (car, bus, train, subway, motorcycle, and bicycle) for eight impact indicators. Fine particulate matter (PM2.5 ) emissions and health impacts are incorporated in the assessment using intake fractions that differentiate between urban and nonurban emissions, combined with an effect factor. The potential benefits of different strategies for reducing environmental impacts are illustrated. The results demonstrate the need for comprehensive approaches that avoid problem-shifting among transportation-related strategies. Policies aiming to improve the environmental performance of urban transportation should target strategies that decrease local emissions, life-cycle impacts and health effects.